2007
DOI: 10.1149/1.2719563
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution of Annealed Ruthenium–Nitrogen Films

Abstract: Microstructure evolution of Ru layer deposited in N 2 gas has been investigated and compared with that deposited in Ar gas for Cu diffusion barrier application. Deposition of Ru in N 2 results in high N dissolution, seemingly uniformly distributed in the Ru layer. The film microstructure is a mixture of nanocrystals and amorphous Ru instead of the columnar structure observed when deposited in argon. Annealing at T Ͼ 250°C causes N out-diffusion and crystallization of the amorphous Ru. Voids were observed at Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…In the XRD patterns of RuSiN film with the number of SiN x unit cycles of 9 (total numbers of SiN x sub-cycles: 225), it was almost impossible to detect the specific peaks from HCP-Ru, suggesting that a RuSiN film was almost amorphized. It was also reported that by incorporating Ta, N, and TaN into Ru, the polycrystalline columnar grain growth of Ru was destroyed, its grain size was reduced as compared to that of Ru, and the microstructure was changed to nanocrystallite embedded structure in an amorphous matrix, 14 amorphous with some isolated nanocrystals of the order of ∼2 to 3 nm, 23 and amorphous. 15 Though the reason for it is not clear yet, it was suggested that a high level of internal stain due to the incorporation of impurity atoms could promote nanocrystalline structure with shorter range ordering, or even an amorphous structure, in the deposited film.…”
Section: Resultsmentioning
confidence: 99%
“…In the XRD patterns of RuSiN film with the number of SiN x unit cycles of 9 (total numbers of SiN x sub-cycles: 225), it was almost impossible to detect the specific peaks from HCP-Ru, suggesting that a RuSiN film was almost amorphized. It was also reported that by incorporating Ta, N, and TaN into Ru, the polycrystalline columnar grain growth of Ru was destroyed, its grain size was reduced as compared to that of Ru, and the microstructure was changed to nanocrystallite embedded structure in an amorphous matrix, 14 amorphous with some isolated nanocrystals of the order of ∼2 to 3 nm, 23 and amorphous. 15 Though the reason for it is not clear yet, it was suggested that a high level of internal stain due to the incorporation of impurity atoms could promote nanocrystalline structure with shorter range ordering, or even an amorphous structure, in the deposited film.…”
Section: Resultsmentioning
confidence: 99%
“…Further, it has almost half of Ta resistivity and (even very thin) Ru films can act as a diffusion barrier enabling direct plating of copper [196]. Although N addition to Ru leads to a mixed nanocrystalline-amorphous microstructure, N out-diffusion is observed already at low annealing temperatures (Figure 6.9) [200]. However, thin Ru films are not very effective as a Cu diffusion barrier.…”
Section: Barriers For Direct Cu Platingmentioning
confidence: 99%
“…However, pure Ru film exhibits a columnar grain structure; the vertical grain boundaries provide Cu with the high diffusion paths, which lead to early failure of the Ru barrier [11]. Recently, the improvement of Ru barrier-performance against Cu has been widely studied [12][13][14]. Adding extra elements, such as N, P, and Ta as impurities in the lattice matrix of Ru film is a way to enhance Cu diffusion barrier properties [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the improvement of Ru barrier-performance against Cu has been widely studied [12][13][14]. Adding extra elements, such as N, P, and Ta as impurities in the lattice matrix of Ru film is a way to enhance Cu diffusion barrier properties [12,14,15]. Damayanti et al indicated that the dissolved N in Ru film can modify crystalline Ru film trending to an amorphous microstructure [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation